67.5k views
4 votes
A. (-45, -2), (-48, -1), (-49, 0), (-48, 1), (-45, 2)

B. (-2, -53), (-1, -50), (0, -49), (1, -48) (2, -45)

C. (-2, -45), (-1, -48), (0, -49), (1, -48) (2, -45)

A. (-45, -2), (-48, -1), (-49, 0), (-48, 1), (-45, 2) B. (-2, -53), (-1, -50), (0, -49), (1, -48) (2, -45) C-example-1
User Andersr
by
5.0k points

1 Answer

3 votes

Answer:

(-2)^2 - 49

4 - 49 = -45

(-1)^2 - 49 = 1 - 49= -48

(0)^2-49= 0-49=-49

(1)^2-49=1-49=-48

(2)^2-49= 4-49= -45

the solution is either a or c

(x,y) ==> (-45,-2),(-48,-1),(-49,0),(-48,1),(-45,2)

(y,x)==> (-2, -45), (-1,-48), (-0,-49),(1,-48),(2,-45)

Explanation: